PENERAPAN METODE PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 4 MAKERUH KECAMATAN RUPAT KABUPATEN BENGKALIS - Susila Susila; Lazim N Lazim N; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research are (1) To describe the application of problem solving method in improving learning outcomes in science learning for fourth grade of SD Negeri 4 Makeruh Subdistrict of Rupat, Bengkalis Regency, and (2) Describing improvement of learning outcomes in science lesson for grade IV SDN SD Negeri 4 Makeruh District Rupat Bengkalis Regency. Data were collected by observation, observation, document, and test. The result of the research are: (1) there is an increase of student learning activity through the application of problem solving method, (2) there is improvement of student learning outcomes through application of problem solving method, and (3) from 30 students only one student who has not finished after learning activity for two cycles because classified as slow learning students.Keywords: learning outcomes, science learning, problem solving method